Development of heat-mass exchange optimization methods using fractal convolutions of computer tomograms - Становский, Александр Леонидович; Савельева, Оксана Степановна; Прокопович, Игорь Валентинович; Торопенко, Алла Владимировна; Духанина, Марианна Александровна (Eastern-European Journal of Enterprise Technologies, 2014)
It was shown that designing heat-mass exchange processes and devices requires the methods of non-destructive measurement of the real surface area of such an exchange. Since this surface is, usually, very complicated, convolutions of images, obtained in the computer tomograph were proposed. Tomograms of synthetic granite, confirming the technical feasibility of such analysis method and its informativeness in terms of further heterogeneous structure investigation were obtained. Three types of convolutions: convolution in the form of Hausdorff dimensions of the section boundaries, convolution using contraction mapping and convolution using parabolic transformation were considered. The presence of a maximum on the dependence of the heat-mass exchange rate on the working surface convolution results, which allows to formulate and solve the problems of optimizing the parameters of technological processes and designs of heat-mass exchange devices was theoretically justified and experimentally confirmed. Practical testing of the proposed optimization method in designing the packed absorber was performed. As a result of using the proposed method, an increase in the absorber performance by 16-23% without increasing its size was achieved.